Graph Modelling and Transformation: Theory meets Practice - Ermel, Claudia; Ehrig, Karsten (Electronic Communications of the EASST, 2010)
In this paper, we focus on the role of graphs and graph transformation for four practical application areas from software system development. We present the typical problems in these areas and investigate how the respective systems are modelled by graphs and graph transformation. In particular, we are interested in the usefulness of theoretical graph transformation results and graph transformation tools in order to solve these problems. Finally, we characterize concepts and tool features which are still missing in practice to solve the presented and related problems even better. Keywords: graph modelling, graph transformation, graph transformation tools